Desejos, brasilidades e segredos: o negócio do sexo na relação entre clientela espanhola e travestis brasileiras - Silva, Larissa Maués Pelúcio [UNESP] (My University, 2011)
The gender ethinicization and the nationality sexualization are aspects that have been discussed in the relationship between Spanish clients and Brazilian transvestites in the brisk sex business in Spain. Sometimes, in these sexual relationships, which are also business relationships, erotic aspects are associated with exoticism that is not related only to nationality or race, but also to new sexual experiences that are more exciting than those considered conventional practices. Hence, the connection between Brazil and the transgender body, made by some Spanish clients, makes sense only when considering the dense sexual grammar involved in those relationships. These signs were structured based on continual colonial attributions, which have been given fresh meaning by the new migration flow resulting from the broad spread of images and insertion of Brazil into the sexual tourism route. Aiming at fully discussing this proposal, this research is based on the queer theory and on other studies in the literature that focus on the poststructuralist and post-colonial sex market. These tools were used to analyze the data gathered in an ethnographic study carried out in São Paulo, Madrid, and Barcelona, as well as data collected from Spanish websites about sexual interest in transvestites

A etnização do gênero e a sexualização da nacionalidade, são aspectos que tem permeado os encontros entre travestis brasileiras e a clientela espanhola no movimentado negócio do sexo pago. Nesses encontros sexuais/ comerciais, aspectos tomados como eróticos se associam a um exotismo que não se refere apenas à nacionalidade ou raça, mas também a possibilidades de experenciar possibilidades sexuais mais excitantes que as tidas como convencionais. Assim, a vinculação que muitos clientes fazem entre o Brasil e o corpo travesti só pode fazer sentido quando examinamos a densa gramática sexual que permeia essas relações. Para explorar as possibilidades desta proposta recorro às contribuições da teoria queer as quais agrego a reflexões de autoras que tem pensado o mercado do sexo a partir do enfoque pós-estruturalista e pós-colonial. São essas as ferramentas que aciono para pensar os dados colhidos em um trabalho etnográfico que tem seu campo em São Paulo, Madri e Barcelona, assim como em sites espanhóis especializados no interesse sexual por travestis
Keywords: Transnational sex market; Clients; Transvestites; Eroticism and exoticism; Mercado transnacional do sexo; Clientes; Travestis; Erotismo e exotismo